A decade of major vascular trauma: Lessons learned from gang and civilian warfare - Ramdass, MJ (Ann R Coll Surg Engl, 2017)
INTRODUCTION: Trinidad and Tobago is a trans-shipment point for the illegal trade of drugs, arms and ammunition and, as such, has a high incidence of gang-related warfare and drug-related crimes. This has led to a high incidence of gunshot and stab wounds, with associated major vascular injuries. We describe our management strategies learned from a decade of vascular trauma experience. METHODS: A retrospective analysis of age, gender, type of trauma, vessel injured, procedure and outcome for all cases of vascular trauma between 2006 and 2015 at two surgical units in Trinidad and Tobago. RESULTS: There were 198 vascular trauma cases (232 procedures), involving 159 (80%) males at a mean age of 33 years. Gunshots accounted for 103 (52%) cases, followed by stabs/chops (n=50; 25%) and lacerations (n=15; 8%). The most commonly injured vessels were the radial/ulnar arteries (n=39; 20%) and the superficial femoral artery (n=37; 19%). There were seven pseudoaneurysms and three traumatic arteriovenous fistulae. Repair techniques included primary (n=82; 35%), reversed vein (n=63; 27%), polytetrafluoroethylene (n=58; 25%), oversew (n=24; 10%) and endovascular (n=5; 2%) techniques. There were eight (4%) secondary amputations and eight (4%) deaths. CONCLUSIONS: Major vascular trauma causes significant morbidity and mortality in Trinidad and Tobago, with the majority of cases due to gunshot injuries secondary to gang-related warfare and civilian violence. We compare our experience with that in the literature on the epidemiology and management of vascular trauma.